Analisis Hubungan Pengetahuan terkait Hipertensi dengan Kepatuhan Minum Obat dan Kontrol Tekanan Darah pada Pasien Hipertensi - Mahadri Dhrik; Anak Agung Ngurah Putra Riana Prasetya; Pande Made Desy Ratnasari (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Hypertension is a chronic disease with a high mortality rate, and patient adherence to treatment is still low. Low patient adherence can be caused by several factors, including patient knowledge related to hypertension. In addition, medication adherence is a factor that can affect blood pressure control. This study aimed to analyze the relationship between knowledge, adherence, and blood pressure control in hypertensive patients. This research was conducted at Tk.II Udayana Hospital Denpasar with data collection time, namely February-April 2022. The research design was carried out cross-sectionally using a validated questionnaire. The level of patient knowledge was measured using the Hypertension Knowledge Level Scale (HK-LS) questionnaire, and the level of patient compliance was measured using the Probabilistic Medication Adherence Scale (ProMAS) questionnaire. The patient's blood pressure data has been seen through the patient's medical record in the past three months. The sampling technique in this study used a nonprobability sampling technique with a consecutive sampling approach. The data analysis used to determine the relationship between hypertension knowledge and adherence to taking medication is the Pearson correlation test. Differences in blood pressure control at various levels of adherence were tested with the Kruskal-Wallis test. The results of the analysis of 78 respondents showed that there was a significant relationship between knowledge and medication adherence (p=0.004; r=0.321). For drinking compliance with blood pressure control, there was no significant difference in blood pressure control values at various levels of drinking adherence (p=0.941). Thus knowledge related to hypertension affects medication adherence. However, various factors other than medication adherence are needed to produce reasonable blood pressure control.